Awareness, actions, drivers and barriers of sustainable construction in Chile - Serpell, Alfredo; Kort, Jorge; Vera, Sergio (Technological and Economic Development of Economy, 2013)
The socio-economic conditions of a country and the overall practices of the construction industry towards Sustainable Construction (SC) are critical factors to define the foundations for developing and carrying out a strategic plan to advance in sustainable construction. This paper reports the results of a study about SC practices currently implemented by construction companies and discusses the level of awareness and knowledge, barriers and drivers of SC that were found in building and infrastructure construction companies. In addition, it analyses the influence of the company size on SC practices. Research results show that Chilean construction firms are in an early stage of the path for achieving SC. Their practices towards SC are highly dependent of the company's size and its core business. Main barriers towards SC are the lack of financial incentives, lack of integrated design, and affordability whereas company's tax reduction incentives related to the level of investment effort on SC would be a key governmental policy to promote sustainability. The results of this study might be particularly useful for other countries, particularly developing ones, and for government policy making.